Physiological and Transcriptome Indicators of Salt Tolerance in Wild and Cultivated Barley - Gharaghanipor, Narges; Arzani, Ahmad; Rahimmalek, Mehdi; Ravash, Rudabeh (Frontiers in Plant Science, 2022)
Barley is used as a model cereal to decipher salt tolerance mechanisms, due to its simpler genome than wheat and enhanced salt tolerance compared to rice and wheat. In the present study, RNA-Seq based transcriptomic profiles were compared between salt-tolerant wild (Hordeum spontaneum, genotype no. 395) genotype and salt-sensitive cultivated (H. vulgare, ‘Mona’ cultivar) subjected to salt stress (300 mM NaCl) and control (0 mM NaCl) conditions. Plant growth and physiological attributes were also evaluated in a separate experiment as a comparison. Wild barley was significantly less impacted by salt stress than cultivated barley in growth and physiology and hence was more stress-responsive functionally. A total of 6048 differentially expressed genes (DEGs) including 3025 up-regulated and 3023 down-regulated DEGs were detected in the wild genotype in salt stress conditions. The transcripts of salt-stress-related genes were profoundly lower in the salt-sensitive than the tolerant barley having a total of 2610 DEGs (580 up- and 2030 down-regulated). GO enrichment analysis showed that the DEGs were mainly enriched in biological processes associated with stress defenses (e.g., cellular component, signaling network, ion transporter, regulatory proteins, reactive oxygen species (ROS) scavenging, hormone biosynthesis, osmotic homeostasis). Comparison of the candidate genes in the two genotypes showed that the tolerant genotype contains higher functional and effective salt-tolerance related genes with a higher level of transcripts than the sensitive one. In conclusion, the tolerant genotype consistently exhibited better tolerance to salt stress in physiological and functional attributes than did the sensitive one. These differences provide a comprehensive understanding of the evolved salt-tolerance mechanism in wild barley. The shared mechanisms between these two sub-species revealed at each functional level will provide more reliable insights into the basic mechanisms of salt tolerance in barley species.